You signed in with another tab or window. Reload to refresh your session.You signed out in another tab or window. Reload to refresh your session.You switched accounts on another tab or window. Reload to refresh your session.Dismiss alert
個 example 已經多咗少少嘢,其實真係純粹係個 assumption 度 assume 埋啲你唔需要嘅 hypothesis only。
如果真係要用返 formal language 去寫
你已經有 s(k) -> s(k+1)
你係可以證到
[s(k) -> s(k+1)] -> [s(1) ^ s(2) ^ ... ^ s(k) -> s(k+1)]
= [not s(k) v s(k+1)] -> [not {s(1) ^ s(2) ^ ... ^ s(k)] v s(k+1) (implication)
= not [not s(k) v s(k+1)] v [not {s(1) ^ s(2) ^ ... ^ s(k)] v s(k+1) (implication)
= [s(k) ^ not s(k+1)] v [not {s(1) ^ s(2) ^ ... ^ s(k)] v s(k+1) (de morgan)
= [s(k) ^ not s(k+1)] v [not s(1) v not s(2) v ... v not s(k)] v s(k+1) (de morgan)
= [s(k) ^ not s(k+1)] v not s(1) v not s(2) v ... v [not s(k) v s(k+1)] (associativity)
= [s(k) ^ not s(k+1)] v not s(1) v not s(2) v ... v not [ s(k) ^ not s(k+1)] (de morgan)
= True (a or not a)
[T(k) -> S(k+1)] -> [T(k) -> T(k+1)]
= [not T(k) v S(k+1)] -> [not T(k) v T(k+1)] (implication)
= not [not T(k) v S(k+1)] v [not T(k) v T(k+1)] (implication)
= (T(k) ^ not S(k+1)) v not T(k) v T(k+1) (de morgan)
= not S(k+1) v not T(k) v T(k+1) (distribute and cancel the side with T(k) or not T(k) - that term is always true and you can cancel true in disjunction)
= not S(k+1) v not T(k) v (T(k) ^ S(k+1)) (definition of T(k+1))
= not (s(k+1) ^ T(k)) v (T(k) ^ S(k+1)) (de morgan)
= true (a or not a)
個人話係
如果你 base on 前面 n 句,證到第 n + 1 句
咁你 base on 前面 n 句,證到前面 n + 1 句 (因為 base on 前面 n 句,證前面 n 句係 trivial)
reacted with thumbs up emoji reacted with thumbs down emoji reacted with laugh emoji reacted with hooray emoji reacted with confused emoji reacted with heart emoji reacted with rocket emoji reacted with eyes emoji
-
題目 : Exercise 0.3.2
以下是 @ceciliachan1979 嘅補充說明
個 example 已經多咗少少嘢,其實真係純粹係個 assumption 度 assume 埋啲你唔需要嘅 hypothesis only。
如果真係要用返 formal language 去寫
你已經有 s(k) -> s(k+1)
你係可以證到
個人話係 你 assume 'a',可以證到 'x'
你 assume 'a', 'b', 'c', 'd', 'e',一樣證到 'x'
如果呢點唔係 trivial,加返落去都冇問題嘅。
同樣道理,係反向嘅時候其實都有同樣嘅 logic 位
你已經有 T(k) -> S(k+1),要證 T(k) -> T(k+1) 其實只係加返一個 T(k) -> T(k)
個人話係
如果你 base on 前面 n 句,證到第 n + 1 句
咁你 base on 前面 n 句,證到前面 n + 1 句 (因為 base on 前面 n 句,證前面 n 句係 trivial)
個人覺得咁 trivial 嘅嘢唔需要咁 formal
Beta Was this translation helpful? Give feedback.
All reactions